Introduction : Social Sustainability in Business Education - Šilenskytė, Aušrinė; Cordova, Miguel; Schmitz, Marina A.; Toh, Soo Min (Palgrave Macmillan, 2024)
In the introduction, we frame the importance of social sustainability for business and broader society, and explain why business education has substantial power to foster it, making a significant contribution to the global collective effort aimed at achieving economic, social, and environmental sustainability. To this end, we elaborate on the concept of social sustainability, clarify how it connects to the environmental and economic dimensions of sustainability, and explain which of the United Nations’ Sustainable Development Goals (SDGs) emphasize issues related to social sustainability. Additionally, we summarize teaching innovations documented from every continent in the world that are featured in this handbook. The richness of the voices and perspectives featured, as well as their cross-disciplinarity, are at the heart of the ethos of this handbook, and we elucidate how and why higher education institutions, managers of business programs, educators, and researchers would benefit from the featured contributions. Finally, we outline some tips on how to use the handbook effectively when researching social sustainability and when implanting social-sustainability-focused SDGs in business programs, courses, and/or lesson plans in different parts of the world, considering the contextual needs of the learner, the business education provider, and the educator.
Keywords: business education; higher education; Sustainable Development Goals; teaching innovations; social sustainability; fi=Strateginen johtaminen|en=Strategic Management|